Pengaruh Lingkungan Kerja Fisik dan Lingkungn Kerja Non-fisik Terhadap Kepuasan Kerja Pegawai pada Kantor Dinas Perhubungan Kabupaten Gowa - Nur Annisa; Burhanuddin Burhanuddin; Tenri Sayu Puspitaningsih Dipoatmodjo (UNIVERSITAS MARITIM AMNI SEMARANG, 2024)
This research aims to determine empirically the influence of the physical work environment and non-physical work environment on employee job satisfaction at the Gowa Regency Transportation Service office. The population used is all Civil Servants at the Gowa Regency Transportation Service office. The sample used was 51 employees who were used as respondents. This research is quantitative research with a descriptive approach using primary data. Technical data analysis was carried out using the multiple linear regression method using Statistical Product and Service Solution (SPSS) version 25. The results of this study indicate that the physical work environment has a positive and significant effect on employee job satisfaction, and the non-physical work environment has a positive and significant effect on employee satisfaction, and the physical work environment and non-physical work environment simultaneously have a positive and significant effect on employee job satisfaction.